Characteristics of Babies Born to HIV Positive Mothers in Ulin General Hospital Banjarmasin January – December 2020 - Ruth Angelina Siregar; Pudji Andayani; Pricilia Gunawan Halim (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
The high incidence rate of mothers with Human Immunodeficiency Virus (HIV) increases the potential of vertical transmission to the baby. HIV is a group of retroviruses that attacks the immune system. It can be transmitted through the exchange of various body fluids from the infected person, such as blood, breast milk, semen, and vaginal fluids. HIV can also be passed from a mother to her child during pregnancy and childbirth. Transmission of HIV from mother to baby is called a vertical transmission and may occur in 3 ways, including antenatal, perinatal, and postnatal (breast milk). This study aims to describe the characteristics of babies born to HIV positive mothers at Ulin General Hospital, Banjarmasin during January-December 2020. This is a descriptive observational study using secondary data from medical records of the babies born to HIV mothers at Ulin General Hospital, Banjarmasin. We include 13 cases of babies born to HIV-positive mothers. The characteristics of the babies were male (53.8%), born without asphyxia (92%), has normal birth weight (84.6%), full-term (92%), and 84.6% of babies were delivered through C-section. The results showed that it is necessary to work together with various fields to get early intervention for each baby.